Juozas Aputis’s Short Story “It Is Unfortunate That You Are Left Alone”: Bronius Radzevičius’s Implication - Vaitiekūnas, Dainius (Colloquia, 2018)
The author of this article seeks to describe the effect of a dedication to the writer Bronius Radzevičius (1940–1980) upon the short story “It’s Unfortunate That You Are Left Alone,” written by his friend Juozas Aputis. This work was published in Aputis’s collection of short stories titled Keleivio novelės (A Traveller’s Stories, 1985). Radzevičius’s collection of short prose, Link Debesijos (Toward the Debesija) was published in 1984, followed in 1985 by the full, two-volume edition of Radzevičius’s novel Priešaušrio vieškeliai (The Predawn Roads), the second volume of which was edited by Aputis.A narratological analysis of the Aputis story dedicated to Bronius Radzevičius reveals that the dedication can be understood as having a metanarrative effect: it can be seen as a second narrative within the story and one which envelops the story’s own narrative. The story’s narrative can be seen as connected to the enveloping narrative by, at the very least, a thematic connection which encourages us to look for a parabolic connection between these two narratives. The paratext of the dedication, which establishes a relationship between the work of these two authors, encourages us the read both the title of Aputis’s story and the text itself differently. For this very reason the dedication can be compared to the laconic foreword, in which the main rhetorical device is the ellipsis.
Keywords: Juozas Aputis; Bronius Radzevičius; dedication; narrator; narratology